LITERATURE REVIEW : PENGGUNANAAN TEKNIK ENDORPHINE MESSAGE TERHADAP PENURUNAN NYERI PERSALINAN PADA IBU BERSALIN KALA I - Lea Ingne Reffita; Ummi Halfida; Mohammad Eko Pranoto (Poltekkes Kemenkes Medan, 2022)
in the labor process, pain during labor due to uterine tightening, expansion along with the occurrence of a thinning cervix, along with the process of descent of the fetus during labor. Pain during labor causes anxiety and discomfort to the mother in the process of giving birth. The purpose of this study was to examine the efficacy of endorphin massage as a pain reliever during labor. Competency 3 (Pregnancy Care) basic knowledge of paragraph 22 (relaxation techniques and strategies to relieve pain in preparation for labor and birth). Non-pharmacological therapy that is very effective in reducing the intensity of labor pain is endorphin massage. The design applied in this study is a literature review study, researchers found about the effectiveness of endorphin massage in as many as (n=20) journals after entering the inclusion criteria in this study articles that could be used as many as (n=10) articles. After conducting a review of all the journals that the researchers studied, they obtained the same result, namely that endorphin massage is very effective as an alternative to reduce labor pain for pregnant women who are in the first stage of labor.